ANALISIS FAKTOR-FAKTOR EKSPOR PRODUK PERTANIAN INDONESIA KE NEGARA KURANG BERKEMBANG - Qiki Qilang Syachbudy; Muhammad Firdaus; Heny Kuswanti Suwarsinah Daryanto (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2017)
This study aims to analyze the potential of new export markets for Indonesian agricultural products and analyze the factors that affect the export of agricultural products LDCs. The method used was Export Product Dynamics (EPD) and Gravity Model. The study focused on Indonesian agricultural exports to 36 countries which have a GDP per capita below US 3.500. The study found that Indonesia has relationships that is different among commodities. For tea, Indonesia has trade relation with Cambodia, Kenya, and Pakistan. For palm oil, Indonesia has trade relation with Bangladesh, Togo, Sierra Leone, Guinea, Benin, Mozambique, Tanzania, Nigeria, Yemen, Cameroon, Senegal, Pakistan, and Ghana. For coconut, Indonesia has good trade relation with Bangladesh, Tanzania, and Pakistan. For Sugar, Indonesia has trade relation to Madagascar, Kenya, Yemen, Cambodia, Bangladesh, Ghana, and Pakistan. Factors affecting the demand of tea are gross domestic product of importer countries and economics distance. Furthermore, factor influencing the trading of palm oil are world price, gross domestic product of importer countries and economics distance. While, coconut and sugar trading is affected by world price and economics distance. Thus, it can be said that the potential for new export markets for Indonesian agricultural products in the context of South-South Cooperation has a good chances.